MANAJEMEN PERTUNJUKAN DRAMA MUSIKAL “KI HAJAR SALOKANTARA” DI SALOKA THEME PARK SEMARANG : ANALISIS FUNGSI PLANNING, ORGANIZING, ACTUATING, DAN CONTROLLING - Khalila Shafira; Rimasari Pramesti Putri (Universitas Negeri Makassar, 2026)
This study aims to describe the implementation of POAC management functions in the musical drama Ki Hajar Salokantara at Saloka Theme Park Semarang, and to identify structural obstacles and managerial solutions applied by the production team. This study employs a descriptive qualitative approach with one primary informant, namely the SAKA coordinator who has been directly involved in performance management for seven years. Data were collected through direct observation, in-depth interviews, and documentation study conducted on 15 February 2026 at Arena Jejogedan, Saloka Theme Park. Data validity was ensured through technique triangulation by confirming the same information using three different collection methods. Data analysis followed the interactive model of Miles, Huberman, and Saldana through stages of data reduction, data display, and conclusion drawing. The findings indicate that all four POAC functions have been operationally implemented but have not been formally documented. Planning was conducted verbally without written procedures, organizational structure remains centralized on a single coordinator without a structured delegation mechanism, actuating faced motivational challenges due to the repetitive nature of performances, and evaluation was carried out without measurable indicators. Recommended solutions include drafting written standard operating procedures for production and establishing an internal mentoring system to distribute managerial capacity more evenly within the team.